Rotational motion investigation in seismology – remote sensing by an optical fiber seismograph - Kurzych, Anna T.; Jaroszewicz, Leszek R.; Dudek, Michał (Advanced Optical Technologies, 2024)
This paper aims to present data recorded by a three-axial Fiber-Optic Rotational Seismograph (FORS). The laboratory and field tests showed a high correlation coefficient above 99% between two seismographs signals during the external disturbance, with an amplitude ranging from 0.5 mrad/s to 1.2 rad/s. This is achieved by ensuring a 100 ns time synchronization in the systems. At the same time, the Allan Variance analysis was applied to determine the basic parameters of random errors of the presented seismographs. The performed analysis indicates the angular random walk of 35-45 nrad/s/√Hz and a bias instability below 50 nrad/s. FORS offers the widest dynamic range available, at 170 dB, which is crucial during rotational seismology exploration due to its wide range of interest from seismology to engineering applications. Finally, a field research is also presented during an explosion in a closed limestone quarry in the border area.